A REVIEW ON PSYCHOSIS AND ANTI-PSYCHOTIC PLANTS - YADAV, MONU; Parle, Milind; Kadian, Monika; Sharma, Kailash (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Psychosis (schizophrenic, schizoaffective, and affective illnesses) is a group of serious illnesses that affect the mind. About 1% of the population suffers from psychosis worldwide and increases for those, whose closer family member have suffered with the disorder. Common symptoms of psychosis are hallucinations, delusions, flat affect, forgetfulness, alogia, avolition, and anhedonia. Currently available marketed drugs like chlorpromazine, haloperidol, clozapine, risperidone, and olanzapine have some serious adverse effects such as dizziness, diabetes, weight gain, tardive dyskinesia, neuroleptic malignant syndrome, sexual dysfunction, agitation, and sedation. There is no satisfactory remedy available for prevention and management of psychosis. Therefore, the demand for herbal medicine is increasing. This article collects the information about the possible plants and dietary supplements to improve symptoms of psychosis with no side effect. The present review discusses about anti-psychotic plants, its biological source, common name, and other biological activities, which are helpful for researchers to development new anti-psychotic herbal formulations. Keywords: Psychosis, Anti-psychotic drugs, Dietary supplements, Anti-psychotic plants.